2001
DOI: 10.1034/j.1399-0039.2001.057001015.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of soluble HLA‐G plasma levels with HLA‐G alleles

Abstract: Soluble HLA-G (sHLA-G) molecules are found in the peripheral blood of healthy females and males, in cord blood and in amniotic fluids and discussed to be a mediator in maternal-fetal tolerance. In this study we investigated whether there are allele-specific differences in expression of sHLA-G molecules. For this, the sHLA-G plasma concentrations of 94 healthy unrelated individuals were measured by ELISA and correlated to their HLA-G genotypes, as determined by sequence analysis of exon 2 and 3 of the HLA-G gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
5
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(177 citation statements)
references
References 41 publications
(42 reference statements)
9
160
5
2
Order By: Relevance
“…Moreover, it was shown that in M8 cells treated with arsenite, HLA-G6 was the first transcript induced (40). It thus appears that HLA-G transcripts that contain intron 4 might be preferentially expressed after HLA-G gene activation in some cell lines, suggesting tight control of HLA-G alternative splicing, which in part may be linked to the HLA-G allelic form (65). For example, we can postulate that mutations in HLA-G gene splicing sites might favor the expression of intron 4-containing transcripts in some cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that in M8 cells treated with arsenite, HLA-G6 was the first transcript induced (40). It thus appears that HLA-G transcripts that contain intron 4 might be preferentially expressed after HLA-G gene activation in some cell lines, suggesting tight control of HLA-G alternative splicing, which in part may be linked to the HLA-G allelic form (65). For example, we can postulate that mutations in HLA-G gene splicing sites might favor the expression of intron 4-containing transcripts in some cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude that HLA-G-positive patients may carry out specific HLA-G alleles associated with high HLA-G production. 30 In addition, the degree of histoincompatibility between donor and recipient may play a role in stimulating HLA-G production. Today, heart transplantation has been established as a valuable therapeutic approach to end-stage heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…19 In this study, the HLA-G*0103 was associated with protection against HPV lesions when patients considered as a whole were compared to controls. In addition, all the individuals presenting the G*0103 allele in this study were homozygous for this allele (confirmed by sequencing analysis), indicating that the associations with the G*0103 allele or G*0103/G*0103 genotype were not independent observations.…”
Section: Hla-g In Patients Stratified According To Lesion Severity Anmentioning
confidence: 99%
“…18 HLA-G alleles may influence the plasma levels of soluble HLA-G (sHLA-G). 19 In addition, a 14 bp insertion/deletion polymorphism has been reported in the 3 0 -untranslated region (UTR) of exon 8. 20 HLA-G alleles exhibiting the 14 bp insertion ( þ 14 bp) undergo an alternative splicing that removes 92 bases from 3 0 UTR, 21 influencing the stability of HLA-G mRNA.…”
Section: -15mentioning
confidence: 99%